Languages in dreams: a diary study - Dollnick, Dilay; Schredl, Michael (International journal of dream research, 2024)
Language is a vital part of our waking life, according to the continuity hypothesis language should also play an important role in dreams. Overall, 78 participants completed an online questionnaire regarding languages and dreaming. Of those 70 completed a two-week dream diary eliciting language use in waking life and dreaming. The results indicated that with an increasing exposure to a language during the day, the respective language occurred more often in subsequent dreams. In addition, our results also indicate that the native language occurs relatively more often in dreams compared to the amount of native language use in waking life. Our findings are in line with the continuity hypothesis: language is indeed an important ingredient of dreams. An interesting topic for future research would be studying language choice in dreams, i.e. whether choosing a language based on features such as setting, conversation partner, situation, and identity in dreams is similar to choosing the appropriate language in waking life.
Gesehen am 17.04.2024